Comparison of gemcitabin, cisplatin, and dexamethasone (GDP), CHOP, and CHOPE in the first-line treatment of peripheral T-cell lymphomas. Issue 9 (20th October 2016) - Jia, Bo; Hu, Shaoxuan; Yang, Jianliang; Zhou, Shengyu; Liu, Peng; Qin, Yan; Gui, Lin; Yang, Sheng; Lin, Hua; Zhang, Changgong; Xing, Puyuan; Wang, Lin; et al.
Abstract : Objectives : Optimal chemotherapy regimen for peripheral T-cell lymphomas (PTCL) has not been fully defined. This study aimed to evaluate the optimal chemotherapy regimen in the first-line treatment for PTCL patients. Methods : Between 2003 and 2014, 93 consecutive patients with PTCL were enrolled in this study. Of 93 patients, 42 patients received CHOPE, 40 patients with CHOP, and 11 patients with GDP regimen. Results : Response could be evaluated in 88 of 93 patients at the end of primary treatment. The CR rate for patients received CHOP ( n = 38), CHOPE ( n = 39), and GDP ( n = 11) were 28.9, 51.3, and 45.5%, respectively, ( P = 0.132) with an ORR of 65.8, 76.9, and 90.9%, respectively, ( P = 0.210). The median follow-up time was 17.1 (1.4–108.3) months. Median progression-free survival (PFS) in CHOP ( n = 40), CHOPE ( n = 42), and GDP ( n = 11) groups were 6.0, 15.3, and 9.7 months ( P = 0.094) with 1-year PFS of 35.0, 54.8, and 45.5%, respectively, ( P = 0.078). One-year OS for patients received CHOP ( n = 40), CHOPE ( n = 42), and GDP ( n = 11) were 65.0, 83.3, and 100%, respectively, ( P = 0.013) (CHOP vs CHOPE, P = 0.030; CHOP vs GDP, P = 0.024; CHOPE vs GDP, P = 0.174). Conclusion : CHOPE has a trend to improve CR rate, 1-year PFS and OS compared with CHOP alone. GDP shows promising efficacy which worth further exploration in large cohort studies. Clinical experience presented in this study may serve as reference for future large cohort studies.